(untitled) (REMUNOM, 2025)
Introduction: The HLA system plays a key role in immune responses to vaccines by presenting antigens and activating lymphocytes. Its high genetic variability explains differences in vaccine efficacy among individuals and populations. Purpose: To evaluate the influence of HLA polymorphisms on vaccine-induced immune responses, identifying alleles associated with strong protection or vaccine failure. Methodology: An integrative literature review (2015–2025) was conducted in PubMed, SciELO, and Web of Science, including original articles and systematic reviews addressing the relationship between HLA alleles and vaccine response in humans. Results and discussion: Alleles such as HLA-DRB115 and HLA-DQB106 were linked to strong responses to hepatitis B and influenza vaccines, whereas HLA-DRB103 and HLA-DQB102 were associated with hyporesponsiveness to the MMR vaccine and some COVID-19 vaccines. Differences in antigen presentation by class I and II molecules affect both humoral and cellular immunity, and allele frequency varies across populations. Final considerations: HLA genetic diversity is a determinant of vaccine response, supporting the need for personalized immunogenetic strategies.